Penggunaan Media Digital Interaktif terhadap Motivasi dan Hasil Belajar Matematika Siswa - Nursyahira, Putri; Mawaddah, Dinda; Indahyani, Nurul; Maisaroh, Siti; Lubis, Reza Handika Winata (Medan Resource Center, 2024)
The increasing role of technology in the 21st century has significantly impacted various fields, including education. Students today frequently use digital devices for studying, entertainment, and leisure activities, which directly influences their learning motivation. Mathematics, as a fundamental subject taught from elementary school, requires strong learning motivation to help students grasp abstract concepts and develop logical, analytical, critical, and creative thinking skills. However, many students still exhibit low motivation in learning mathematics. This study aims to analyze the effectiveness of interactive learning media in enhancing students' motivation to learn mathematics. A literature study method was employed to examine previous research findings on this topic. The results indicate that the use of interactive media significantly improves students’ motivation and learning outcomes. Furthermore, students display a more positive attitude toward mathematics when learning through interactive media, feeling more engaged and motivated. These findings suggest that interactive media can serve as an effective alternative in mathematics education to foster student enthusiasm and achievement.